Labor Restructuring in China : Toward a Functioning Labor Market - Dong, Xiao-yuan (2012)
This paper examines the patterns and determinants of the labor restructuring process in China using two large firm-level datasets for the period between 1998 and 2002. We find that the public sector has undergone substantial labor retrenchment. The removal of employment guarantees for state workers has led to substantial employment shifts both within and between sectors. As compared to many Central and East European countries and the countries of the Commonwealth of Independent States in their early phases of transition, China has experienced a more synchronized pace of job destruction and creation as well as higher rates of excessive reallocation. Our results also show that the employment adjustment and downsizing process has been driven largely by market forces. We find a notable resemblance in the patterns of enterprise response to demand shocks across the public and the private sectors.